2017
DOI: 10.1016/j.cct.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of ASTEROID 2, a randomized, placebo- and active comparator-controlled study to assess the efficacy and safety of vilaprisan in patients with uterine fibroids

Abstract: The placebo- and active comparator-controlled trial ASTEROID 2 is the first study to evaluate systematically the efficacy and safety of different treatment regimens of PRMs in women with UFs. The findings of this study will direct the planning of future clinical trials of vilaprisan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Others have advocated a percentage reduction in score; values of 20-50% have been reported [36,58,59,63,[99][100][101][102][103][104][105]. If the treatment goal is amenorrhea (PBAC score < 2), the endpoint is clearly defined [54,[106][107][108][109]. The aim of several reports is just to detect a significant difference in MBL reduction between different treatments for HMB.…”
Section: Recognition Of Limitationsmentioning
confidence: 99%
“…Others have advocated a percentage reduction in score; values of 20-50% have been reported [36,58,59,63,[99][100][101][102][103][104][105]. If the treatment goal is amenorrhea (PBAC score < 2), the endpoint is clearly defined [54,[106][107][108][109]. The aim of several reports is just to detect a significant difference in MBL reduction between different treatments for HMB.…”
Section: Recognition Of Limitationsmentioning
confidence: 99%
“…12 Vilaprisan is a novel SPRM currently in the late stages of clinical development. 13 The history of the development of SPRMs cannot be separated from the simultaneous evolution of a classification system for the unique endometrial changes accompanying SPRM treatment. The concerns initially arose when early studies reported high rates of endometrial hyperplasia following treatment with mifepristone.…”
Section: The Pastmentioning
confidence: 99%
“…Two novel SPRMs (oral vilaprisan and orally or vaginally administered telapristone acetate) are currently in development for management of UF. 13 Additional new agents or therapeutic strategies may also emerge based on new insights into the effects of PR and their tissuespecific effects.…”
Section: Treatment Options For Symptomatic Uterine Fibroidsmentioning
confidence: 99%
“…ASTEROID II is a phase 2 randomised, placebo-controlled study assessing the efficacy and safety of vilaprisan in patients with uterine fibroids and comparing its effects to UPA. 37 …”
Section: Selective Progesterone Receptor Modulators and Upamentioning
confidence: 99%